Auditoría operacional en las empresas de transporte terrestre de carga pesada - Urueta Chiquito, Joselyn Daniela (2021)
The research project analyzes the operations of the heavy cargo transport sector, and has the purpose of contributing through an operational audit, the observation of the operational processes to identify the weaknesses of the internal control, integrate planning processes and verify the operability of financial management that increases the effectiveness and efficiency of the activities of the business line and favorably influences the liquidity of the companies, providing useful processes and / or tools to the sector that mitigate the occurrence of errors and promote growth. The first chapter is framed in the statement of the problem, the analysis, the exposition of the causes and possible effects in the heavy cargo transport sector, both the general and specific objectives and the justification of the study are also determined..........